Improving the Competitiveness of Educational Institutions through Marketing Mix Management at Islamic Elementary School - Abdul Karim; Ashif Az Zafi; Rochimuzzama Rochimuzzama (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThis study aims to answer the problem of how the competitiveness of Public Islamic Elementary School 1 Pati, Central Java and how to implement Islamic Elementary School-based education marketing mix management in increasing competitiveness in new student admissions. To obtain data, the research uses a naturalistic qualitative approach with multiple methods, namely interviews, observations, and document reviews. This research was conducted at Public Islamic Elementary School 1 Pati, Central Java. Sources of data were obtained from committee administrators, teachers, parents, and the community in Public Islamic Elementary School 1 Pati. The data analysis process is carried out by collecting data, reducing data, displaying data, and drawing conclusions. The results showed that Public Islamic Elementary School 1 Pati carried out various socialization activities aimed at getting a large number of students. This is expected to be able to foster satisfaction for school residents which has an impact on the development of community sympathy. The success of Public Islamic Elementary School 1 Pati in gaining victory in the competition between educational institutions at the elementary level is due to successfully implementing marketing mix management that combines several elements, including products, financing, location, promotion, human resources, and facilities that are able to foster competitive and comparative advantages.Keywords: marketing mix management, madrasah competitiveness, education management strategy.AbstrakPenelitian ini bertujuan untuk menjawab permasalahan bagaimana daya saing Madrasah Ibtidaiyah Negeri (MIN) 1 Pati, Jawa Tengah dan bagaimana implementasi manajemen bauran pemasaran pendidikan berbasis Madrasah dalam meningkatkan daya saing pada penerimaan peserta didik baru. Untuk mendapatkan data, penelitian menggunakan jenis pendekatan kualitatif naturalistik dengan multi metode, yaitu wawancara, pengamatan, dan penelaahan dokumen. Penelitian ini dilaksanakan di MIN 1 Pati. Sumber data didapat dari pengurus komite, guru, orang tua siswa dan masyarakat di lingkungan MIN 1 Pati. Proses analisis data dilakukan dengan pengumpulan data, reduksi data, display data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa MIN 1 Pati melaksanakan berbagai kegiatan sosialisasi yang bertujuan untuk mendapatkan peserta didik dalam jumlah besar. Hal ini diharapkan mampu menumbuhkan kepuasan bagi warga sekolah yang berdampak pada berkembangnya rasa simpati masyarakat. Keberhasilan MIN 1 Pati memperoleh kemenangan dalam persaingan antar lembaga pendidikan di tingkat dasar dikarenakan berhasil mengimplementasikan manajemen bauran pemasaran yang memadukan beberapa unsur, meliputi produk, pembiayaan, lokasi, promosi, sumber daya manusia, dan sarana yang mampu menumbuhkan keunggulan kompetitif dan komparatif.Kata kunci: manajemen bauran pemasaran, daya saing madrasah, strategi manajemen pendidikan